Integrating Reason, Logic, and Islamic Epistemology for Holistic Science in Modern Education - Tatang Muh Nasir; Wawan Purnama; Erni Haryanti; Dadang Komara; Zohaib Hassan Sain (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2025)
This study addresses the growing concern over the decline of students’ critical thinking skills and the limited integration of scientific knowledge with ethical and spiritual values in modern education. It aims to examine how reasoning, logic, and Islamic epistemology can be integrated to develop a holistic approach to science education. Employing a qualitative phenomenological method, data were collected through semi-structured interviews with students from both general and Islamic educational backgrounds and analyzed using thematic analysis. The findings reveal that students actively use inductive and deductive reasoning in academic and everyday contexts, while logic serves as a systematic framework for constructing valid conclusions. Furthermore, sources of knowledge are understood as a combination of empirical experience, rational thinking, and spiritual guidance, including revelation and intuition. These elements are interconnected and form a comprehensive epistemological framework. The study highlights that integrating rational, empirical, and spiritual dimensions can enhance curriculum design and pedagogical practices. This integration contributes to fostering critical thinking, ethical awareness, and holistic character development, offering a balanced and relevant educational paradigm for addressing contemporary global challenges.